Effects of dissolved oxygen and nutrient loading on phosphorus fluxes at the sediment–water interface in the Hai River Estuary, China. (May 2018) - Kang, Mengxin; Peng, Sen; Tian, Yimei; Zhang, Haiya
Abstract: The effects of dissolved oxygen and nutrient loading on the concentrations and species of phosphorus at the sediment–water interface were evaluated under laboratory conditions. The results showed that the redox potential was significantly correlated with the total phosphorus, total dissolved phosphorus, total nitrogen, ammonium and nitrate nitrogen levels in an aerobic setting, but no significant correlations were observed under anaerobic conditions. The dynamic equilibrium between the overlying water and sediment tended to balance out over time, and the concentration gradient reduced, when the nutrient loading was changed. The greatest variation was observed in the level of iron/aluminum-bound phosphorus, while the calcium-bound phosphorus and organic phosphorus contents showed relatively minor changes. This study not only illustrates the phosphorus transfer mechanism between sediment and water, but can also contribute to the management and protection of Bohai Bay. Highlights: The concentrations of the TP, TDP, SRP and TN in the anoxic environment were about twice that in the aerobic environment. A change in nutrient load broke the dynamic equilibrium between sediment and water. Fe/Al-P was the most significant control on P flux. Ca-P and OP were minor contributors to the overall P flux.